Building responsive data visualization for the Web - Hinderman, Bill (Indianapolis, IN : Wiley, 2016)
Building Responsive Data Visualization for the Web is a handbook for any front-end development team needing a framework for integrating responsive web design into the current workflow. Written by a leading industry expert and design lead at Starbase Go, this book provides a wealth of information and practical guidance from the perspective of a real-world designer. You'll walk through the process of building data visualizations responsively as you learn best practices that build upon responsive web design principles, and get the hands-on practice you need with exercises, examples, and source code provided in every chapter. These strategies are designed to be implemented by teams large and small, with varying skill sets, so you can apply these concepts and skills to your project right away.--
Introduction -- Part one: creating the responsive web. The mobile web ; Responsive web design tenets ; Working with a flexible grid ; Designing responsive layouts with CSS ; Enhancing with JavaScript -- Part two: creating responsive data visualization. Data design: an abridged history ; Responsive data visualization tenets ; Thinking small ; Asset dependence ; Code-driven visualization ; Building the future-friendly web -- Part three. Additional resources. Resources.
Includes index.
Vendor-supplied metadata.
Keywords: Information visualization; REFERENCE / Questions & Answers; Information visualization; Responsive Webdesign; Datenvisualisierung; Electronic books